1983
DOI: 10.1088/0029-5515/23/7/006
|View full text |Cite
|
Sign up to set email alerts
|

Boundary layer measurements during density clamp in DITE

Abstract: In an Ohmically heated tokamak discharge with low Z e ff values, it is well known that plasma equilibrium requires that the electrostatic force within a magnetic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1984
1984
1986
1986

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…A correlation between energy and particle confinement times has been noted previously. It has been suggested that convective flow in the scrape-off layer, coupling the heat and particle fluxes parallel to the magnetic field, ensures that a decreased energy confinement time produces a decreased particle confinement time [24]. This link could be broken by increased edge radiation or by the production of a collisional boundary layer [11].…”
Section: Discussionmentioning
confidence: 99%
“…A correlation between energy and particle confinement times has been noted previously. It has been suggested that convective flow in the scrape-off layer, coupling the heat and particle fluxes parallel to the magnetic field, ensures that a decreased energy confinement time produces a decreased particle confinement time [24]. This link could be broken by increased edge radiation or by the production of a collisional boundary layer [11].…”
Section: Discussionmentioning
confidence: 99%
“…Poloidal divertor programmes on a large scale have operated on PDX [250], ASDEX [128], and D III [251], following the more modest feasibility studies on T-12 [252] and DIVA [253, 254], and a poloidal divertor is planned for JT-60. A bundle divertor has been tested on DITE [255], and an upgraded version of this device is now operational [256]. Tests of a toroidal divertor have also begun recently [257].…”
Section: Active Impurity Controlmentioning
confidence: 99%
“…For the study of plasma parameters in the scrapeoff layer in tokamaks, classical Langmuir probes have increasingly been applied [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. We had the opportunity to use this method for time resolved measurements of the plasma density and the electron temperature in the limiter shadow of T-10 during a prolonged period of operation in which the limiter configuration was varied over a wide range [24].…”
Section: Introductionmentioning
confidence: 99%
“…17. Power flux determined density limit: The power flux, p rec , necessary for recycling and total power P rec for T-10-like parameters (a = 0.32 m, R = 1.5 m, D L = 0.4 m 2 -s~l, \ 2 = 4 X 10~2 1 m 3 ) as a function of density (see Eqs(14) and (15)).…”
mentioning
confidence: 99%